Legislation and social imaginary in the hierarchy and the wages of the educators of primary in Colombia. 1952-1994 - Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The purpose of this work aims to present that in Colombia there is a legislation for schools, to the educator of primary education level, it is routed according to the public policy that is crystallized in reforms which have stamps according to the political government deliver them at that time. The importance of the study appears from the need to know this historical period in which it is registered in the majority of the histories of life of the teachers that we did in Colombia. On this matter, we wonder on: which are public policies and imaginaries that they have presented in the legislation and financing of the primary school Colombian educator, and the reliability and changeability of the norm come up by the teachers’ syndicates from 1952 to 1994? We are located under the political history and the conceptual frame of the social history of the education and the mentalities.The methodology compared the criteria of government policies in the financing of the education, teachers’ movements across syndicates, teacher’s levels, they allowed us to analyze the impact and the imaginary social one of the Colombian educator. The strategies teachers had to face from the analysis of the legislation up to the concrete cases of historical facts that motivated changes in the regulation of the teaching. Thus, we take as precedents, in the colonial epoch, the reform of 1774 and the XIXth century we based the information on the years 1870 and 1892. In the XXth century we are focused on the period on from 1913 to 1952. The first date when there is established the retirement pension for the teachers and the second one when the teaching performance is regulated. The second period we took up the issue of the Teacher Statute concluded in 1979 with the union of Colombian Federation of Educators (FECODE). FECODE and it is in updated in most of the articles. We ended the third period, Act 115 of 1994 to represent the current policy towards the education sector. The conclusion is that the law has a social imaginary about the teacher mediated through the public policy and in particular the concept of the political parties that have legislated on this educator and not least is the mediation of regional unions and national who has the conception and employment status which have joined other professions are challenging identity and competitiveness.